Is heel prick as safe as we think?. (19th October 2011) - Onesimo, Roberta; Fioretti, Maria; Pili, Stefania; Monaco, Serena; Romagnoli, Costantino; Fundarò, Carlo
Abstract : Purulent lymphadenitis is rare in newborn and is associated with prematurity and invasive procedure. Neonatal staphylococcal infections due to skin interruption during intramuscular vitamin K administration and national metabolic screening programme (heel prick or Guthrie card test) have been already previously described. This is a report of a premature infant who developed an inguinal adenitis as a result of late complications from heel pricks. The diagnosis was made on clinical grounds and confirmed by ultrasound scans. Staphylococcus aureus was isolated. Bacteremia did not occur and the lymphadenitis had a complete resolution with antimicrobial therapy. The heel prick is a well-established procedure in neonatal practice, nevertheless it is not risk-free. The attention to signs of infections is important to avoid complications such as purulent lymphadenitis, abscess formation and septicemia. Best practice prevention and control in minimising the risk of infections are the most important intervention to prevent this complication.